The Control Mechanism of Procedure and the New Panorama of Demand Repetitive Installed by Law Resolution Incident 13.105/2015 - Ana Luíza Zakur Ayres (Revista de Processo, Jurisdição e Efetividade da Justiça, 2016)
The study aims to address the legislative innovations inserted by Law 13.105/2015, specially in relation to the incident Demand Resolution Repetitive therefore be necessary to apply dynamically devices and equipped principles. Will be shown to the expansion and vertical integration competence of the Supreme Court,assigned topics such as weighting values with enticing features in day- to-day trials. Thus , it seeks to analyze the IRDR,from a global perspective, as it aims to define common legal interpretation repetitive individual actions, which should be adopted in all cases in which it arises the same question of law.